المعاملة الضريبية لكبار المكلفين في إطار التشريع الضريبي السوري - الحلاق محمد; عبدالله حبيب (Latakia University Journal - Economic and Legal Sciences Series, 2017)
ركزت هذه الدراسة على شريحة كبار المكلفين، أو كبار دافعي الضرائب في المجتمع الضريبي، وكيفية معاملتهم ضريبياً وفقاً للتشريع ، وذلك نظراً لأهمية هذه الشريحة لما تقدمه من إيرادات ضريبية ضخمة للخزينة العامة مقارنة بباقي المكلفين وكذلك أهمية القطاعات التي تعمل فيها هذه الشريحة (مصارف - شركات تأمين – شركات اتصالات – شركات نفط ) وقد استهل البحث ببيان مفهوم كبار المكلفين، و الخصائص التي تتميز بها هذه الشريحة والمعايير الدولية المتبعة في تحديدهم وكذلك المعايير التي اتبعها المشرع السوري في تحديده لهم، كما بينت الدراسة فيما إذا كان التشريع الضريبي السوري قد خصهم بمعاملة ضريبية متميزة عن بقية شرائح المكلفين، وفيما إذا كانت هذه المعاملة مطبقة فعلاً على أرض الواقع في وحدة كبار المكلفين التي احدثت بموجب القرار رقم 2428/و تاريخ 23/8/2006، ولتحقيق هدف البحث عمد الباحث إلى تصميم استبانة تتألف من 20 سؤالاً وزعت على عينة تتألف عدد من موظفي وحدة كبار المكلفين في دمشق وكذلك عدد من كبار المكلفين ( أفراد- شركات أشخاص - شركات أموال ) وقد توصلت الدراسة إلى أن التشريع الضريبي السوري قد خص هذه الشريحة بقواعد متميزة عن بقية شرائح المكلفين ولكن هذه الخصوصية قد طبقت جزئياً ولم تطبق بشكل كامل على أرض الواقع، وقدمت الدراسة مجموعة من التوصيات التي قد تكون مفيدة للإدارة الضريبية في سورية وللدارسين This study focused on the large taxpayers, or senior taxpayers in the tax community, and how to tax them in accordance with the legislation, given the importance of this segment for its huge tax revenues for the Public Treasury compared to the rest of the taxpayers as well as the importance of the sectors in which this segment operates (banks - Insurance companies - telecom companies - oil companies). This paper starts by assessing the concept of large taxpayer, and the characteristics of this segment and international and the Syrian standards followed in identifying them. The study examines whether the Syrian tax legislation gave them a special taxation treatment different from the rest of taxpayer slices, and whether this treatment is actually implemented on the ground in the large taxpayer unit specified by Resolution No. 2428, dated / 23/8/2006. In order to achieve this goal, the researcher designed a questionnaire composed of 20 questions distributed to a sample comprised of a number of unit staff large taxpayers in Damascus, as well as a number of senior taxpayers (persons- person companies –capital companies). The study found that the Syrian tax legislation has singled out this group by rules distinct from the rest of the taxpayer segments. However, this special treatment has been applied in part and did not apply fully on the ground. The study also offers a set of recommendations that could help both the tax administration and scholars in Syria.